Evaluation of the conventional and synchrotron X-ray tomography applied to heterogeneous oil reservoir rocks (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Carbonate and sandstone reservoirs play an important role in oil industry as they host over 50% of the world’s hydrocarbon reserves. For an accurately assessment of porosity and pore size distribution of such complex pore-network, which affect directly the macroscopic characteristics of multiphase fluid flow, X-ray computed microtomography (micro-CT) emerges as a powerful tool. In contrast to lab-based X-ray micro-CT (XCT), synchrotron X-ray micro-CT (SXCT) images are commonly free of artefacts (i.e. beam hardening) and the unique properties of synchrotron sources enable the X-ray imaging of complex and heterogeneous materials in greater detail, with higher quality, and short acquisition time. This work reports results of cone beam computed microtomography (XCT) in comparison with synchrotron computed microtomography (SXCT) applied to very heterogeneous carbonate and sandstone reservoir rocks. We analyze the quality of the image generated in terms of detection of details and artefacts, the advantages and limitation of each technique, as well as features like contrast, sharpness, and signal-to-noise ratio (SNR). Although SXCT offers significant advantages over XCT, the latter gains in cost of operation, accessibility and user-friendliness.